A review of Morton White's criticisms concerning Clarence Irving Lewis' theory of valuation and normativity - Sánchez García, Victoria Paz (2017)
This paper presents an examination of the critiques put forward by Morton White in his article "Value and Obligation in Dewey and Lewis" (1949), particularly those directed upon C. I. Lewis' conception of normativity and valuation. The critic states that Lewis, in offering an account of the normative character of ethical judgements, fails to consistently articulate his ethical conception with his theory of knowledge. This leads White to conclude that the pragmatist has no solution for the fundamental problem of ethics. I will argue that such conclusion is wrong. The kernel of my argumentation rests in the thesis that White's criticism stems from an inaccurate interpretation of Lewis' conceptualist pragmatism, one that fails to acknowledge the pragmatic apriorism which is the key to a proper understanding of his theory of knowledge and to an explanation of the connection and articulation between valuation and normativity within Lewis' framework. In this line, I will show that, quite on the contrary, Lewis' epistemology highlights his ethical and normative developments, revealing a naturalistic theory of valuation that is the basis upon which normativity pragmatically emerges. I will also maintain that this perspective offers a fruitful conception of values and norms which has not been sufficiently explored; one that confronts ethical skepticism, that can account for the cognitive status of values and norms, and that reclaims the rational character of valuation not only for ethics but also for knowledge and science.
Este artigo apresenta um exame da crítica proposta por Morton White em seu artigo "Valor e obrigação em Dewey e Lewis" (1949), em particular, a aquela voltada para o conceito de normatividade e valoração de C.I. Lewis. A crítica afirma que Lewis, ao oferecer um caráter normativo dos juízos éticos, malogra ao articular consistentemente a sua concepção ética com a sua teoria do conhecimento. Isso leva White a concluir que o pragmatista não possui uma solução para o problema fundamental da ética. Argumentarei que tal conclusão é equivocada. O núcleo da minha argumentação repousa na tese de que a crítica de White se origina de uma interpretação incorreta do pragmatismo conceitualista de Lewis, falhando em reconhecer que o apriorismo pragmático é a chave para o entendimento adequado de teoria do conhecimento e para uma explicação da conexão e articulação entre valoração e normatividade no interior da abordagem de Lewis. Nesta linha, mostrarei que, muito pelo contrário, a epistemologia de Lewis destaca os desenvolvimentos éticos e normativos, revelando uma teoria naturalística de valoração que é a base na qual a normatividade emerge pragmaticamente. Sustentarei, também, que essa perspectiva oferece uma concepção profícua de valores e normas que não têm sido suficientemente exploradas; algo que confronta o ceticismo ético, podendo levar em conta o status cognitivo de valores e normas, e que recupera o caráter racional da valoração não apenas para a ética, mas, também, para o conhecimento e a ciência.
Keywords: Pragmatism; Clarence Irving Lewis; Morton White; Knowledge; Normativity; Valuation; Pragmatismo^lpt; Clarence Irving Lewis; Morton White; Conhecimento; Normatividade; Valoração